2023
DOI: 10.1371/journal.ppat.1011132
|View full text |Cite
|
Sign up to set email alerts
|

Innate sensing of picornavirus infection involves cGAS-STING-mediated antiviral responses triggered by mitochondrial DNA release

Abstract: Cyclic GMP-AMP synthase (cGAS) plays a key role in the innate immune responses to both DNA and RNA virus infection. Here, we found that enterovirus 71 (EV-A71), Seneca Valley virus (SVV), and foot-and-mouth disease virus (FMDV) infection triggered mitochondria damage and mitochondrial DNA (mtDNA) release in vitro and vivo. These responses were mediated by picornavirus 2B proteins which induced mtDNA release during viral replication. SVV infection caused the opening of mitochondrial permeability transition pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 95 publications
3
19
2
Order By: Relevance
“…As a whole, the enhancing effect on FMDV infection observed for the two different compounds tested, known to interfere with the cGAS/STING pathway at different steps, highlights the relevance of this DNA-sensing antiviral route against FMDV infection. This is in agreement with a recent work showing that over-expression of cGAS in porcine kidney cells (PK15) reduced FMDV replication [ 31 ]. We further confirmed the key role of the cGAS enzymatic activity for restraining FMDV infection using recombinant po cGAS-eGFP proteins that were overexpressed either in the wild-type version or as the E200A/D202A inactive form in swine IBRS2 and WSL cells that were subsequently infected with FMDV at different MOI (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As a whole, the enhancing effect on FMDV infection observed for the two different compounds tested, known to interfere with the cGAS/STING pathway at different steps, highlights the relevance of this DNA-sensing antiviral route against FMDV infection. This is in agreement with a recent work showing that over-expression of cGAS in porcine kidney cells (PK15) reduced FMDV replication [ 31 ]. We further confirmed the key role of the cGAS enzymatic activity for restraining FMDV infection using recombinant po cGAS-eGFP proteins that were overexpressed either in the wild-type version or as the E200A/D202A inactive form in swine IBRS2 and WSL cells that were subsequently infected with FMDV at different MOI (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…1b). Although it has been recently reported that FMDV infection induced the decrease of STING but did not affect the expression of cGAS in swine PK15 cells [ 31 ], our data suggest that cGAS could be specifically targeted for degradation during FMDV infection. To test that hypothesis, we first studied the effect of co-expression in HEK293 cells of N-terminal FLAG-tagged porcine cGAS (3xFLAG- po cGAS) together with the FMDV-encoded proteases Lbpro and 3Cpro either in their catalytically active wild-type forms or their inactive counterparts Lb(C51A) [ 33 ] and 3C(H46Y) [ 34 ] carrying mutations in their corresponding active sites.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…It is worth noting that the cGAS-STING signaling can also be regulated by other RNA virus components, such as influenza virus (IAV), encephalomyocarditis virus (EMCV), and lymphocytic choriomeningitis virus (LCMV) [ 73 , 77 79 ]. In IAV infection, researchers have demonstrated that STING-dependent IFN-β gene expression was indispensable for limiting viral replication.…”
Section: Regulation Of Cgas-sting Signaling By Virus-derived Componentsmentioning
confidence: 99%
“…RNA-stimulated signaling is mainly dependent on the adaptor protein mitochondrial antiviral-signaling (MAVS), whereas the signaling triggered by DNA mainly relies on the adaptor protein stimulator of interferon genes (STING) during viral infection [11]. Due to the cross-talk mechanisms between RNA and DNA sensing pathways, the activation of cGAS-STING signaling by RNA viruses has been gradually discovered [12,13]. SARS-CoV-2 infection was reported to activate cGAS-STING through DNA damage, chromatin damage and mitochondrial DNA release [14][15][16].…”
Section: Introductionmentioning
confidence: 99%